Field notes contributed by Paul Martsching, summer 1985 - Martsching, Paulet al (1985)
List of birds and locations contributed by Paul Martsching. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of summer 1985. Epson - sheet feed